Wind-driven residual circulation and related oxygen and nutrient dynamics in the Gulf of Finland (Baltic Sea) in winter. (5th August 2017) - Lips, Urmas; Laanemets, Jaan; Lips, Inga; Liblik, Taavi; Suhhova, Irina; Suursaar, Ülo
Abstract: Establishment of distinct circulation patterns in the Gulf of Finland was observed by a targeted measurement campaign in winter 2013–2014. Strong and long enough up-estuary wind events caused a collapse of vertical stratification and development of a barotropic flow system consisting of an outflow in the open part and inflow along the coasts. In the periods without such unidirectional wind forcing, but when the water column remained weakly stratified, the residual barotropic inflow in the open gulf and outflow along the coasts was observed. In the case of moderate wind forcing, the three-layer vertical stratification and flow structure developed in the gulf. It is shown that the along-gulf expansion of the fresher water tongue in the surface layer as well as the up-estuary penetration of the saltwater wedge in the near-bottom layer followed well the long-term (monthly) changes in the cumulative along-gulf wind stress. The dynamics of the near-bottom saltwater wedge determined the extent of hypoxic bottoms and, as suggested by the firm correlation between the near-bottom phosphate concentration and salinity, the nutrient conditions in the near-bottom layer. The lateral transport of phosphorus, strengthened vertical stratification in the Northern Baltic Proper and suggested increase in the frequency of stratification collapses in the Gulf of Finland in winter predict that the eutrophication effects would not diminish significantly in this estuary in the nearest future. Highlights: Gulf of Finland hydrography, oxygen and nutrients in 2013–2014 were analyzed. Residual circulation and salinity distribution depend largely on wind forcing. Saltwater wedge dynamics control near-bottom oxygen and nutrient conditions. Lateral transport and mixing events affect the near-surface phosphorus pool.